Robust VS4@rGO nanocomposite as a high-capacity and long-life cathode material for aqueous zinc-ion batteries. Issue 28 (13th July 2021) - Chen, Kaijian; Li, Xing; Zang, Jinhao; Zhang, Zhuangfei; Wang, Ye; Lou, Qing; Bai, Yucheng; Fu, Jiatian; Zhuang, Chenfei; Zhang, Ying; Zhang, Leilei; Dai, Shuge; et al.
Abstract : VS4 @rGO nanocomposite is realized as a high-performance cathode in aqueous ZIBs and its energy storage mechanisms are further revealed. Abstract : Although vanadium (V)-based sulfides have been investigated as cathodes for aqueous zinc-ion batteries (ZIBs), the performance improvement and the intrinsic zinc-ion (Zn 2+ ) storage mechanism revelation is still challenging. Here, VS4 @rGO composite with optimized morphology is designed and exhibits ultrahigh specific capacity (450 mA h g −1 at 0.5 A g −1 ) and high-rate capability (313.8 mA h g −1 at 10 A g −1 ) when applied as cathode material for aqueous ZIBs. Furthermore, the VS4 @rGO cathode presents long-life cycling stability with capacity retention of ∼82% after 3500 cycles at 10 A g −1 . The structural evolution, redox, and degradation mechanisms of VS4 during (dis)charge processes are further probed by in situ XRD/Raman techniques and TEM analysis. Our results indicate that the main energy storage mechanism is derived from the intercalation/deintercalation reactions in the open channels of VS4 . Notably, an irreversible phase transition of VS4 into Zn3 (OH)2 V2 O7 ·2H2 O (ZVO) during the charging process and the further transition from ZVO to ZnV3 O8 during long-term cycles are also observed, which might be the main reason leading to the capacity degradation of VS4 @rGO. Our study further improves the electrochemical performance of VS4 in aqueous ZIBs through morphology design and provides new insights into the energy storage and performance degradation mechanisms of Zn 2+ storage in VS4, and thus may endow the large-scale application of V-based sulfides for energy storage systems.